Advancements in NMR and IR Spectroscopy: Enhancing Metabolomics and Disease Diagnostics in the Health Sector: A Comprehensive Review - Saputra, Rizki Rachmad; Ariefin, Mokhamat; Kumalasari, Meiyanti Ratna; Dongoran, Junita; Tampubolon, Mulani Jeni Lestari; Sulistiawati, Putri; Simangunsong, Sri Yulandari; Ariska, Risya; Paksi, Pandu Gizta Rapi; Siska, Amelia; Yanti, Jeddah; Maknun, Luluil (Universitas Islam Indonesia, 2024)
Metabolomics has emerged as a critical field in understanding biological processes and disease mechanisms, necessitating advancements in analytical techniques to handle complex biological samples. This review explores the global landscape of metabolomics, with a focus on the use of spectroscopy and spectrometry. Techniques such as UV-Vis and Fourier Transform InfraRed (FTIR) spectroscopy offer fast and cost-effective metabolite tracing but are limited by their sensitivity, particularly for low-abundance metabolites. Nuclear Magnetic Resonance (NMR) spectroscopy, despite being less sensitive than mass spectrometry (MS), provides unparalleled structural information, distinguishing metabolites with similar mass-to-charge ratios. NMR's capability to detect metabolites in the 1-10 µM range highlights its effectiveness in metabolomics. This review categorizes advancements in these techniques, starting with global contributions to spectroscopy, followed by detailed discussions on FTIR strategies for metabolite tracing, and concluding with NMR's qualitative and quantitative applications in metabolomics and disease diagnostics. The review underscores the continuous development in sample preparation and data integration, enhancing the accuracy and applicability of these techniques, positioning NMR and FTIR as essential tools in modern metabolomic research.